Konseling Islam dalam Menanamkan Nilai-Nilai Spiritual Pelaku Narkoba di Rumah Tahanan Kelas IIB Pinrang - Iskandar; Dahlan, Nurlina (Indonesian Journal of Islamic Counseling, 2022)
The research examines the cultivation of spiritual values ​​for drug offenders in the Pinrang Class IIB Detention Center. The aim of the research is to determine the form of Islamic counseling carried out and efforts to instill spiritual values ​​in the class IIB Pinrang detention center. Data collection techniques are observation, interviews, documentation; Data analysis techniques are data reduction, data presentation, drawing conclusions and verification. The results of this research show that: (1) there are two forms of Islamic counseling for class IIB Pinrang detention center drug offenders, namely: a. Individual counseling is counseling carried out by a supervisor for only one person, b. Group counseling is a form of counseling carried out by counselors by providing guidance to more than one person assisted by inmates. (2) Efforts to instill the spiritual values ​​of drug offenders, namely by forming the Hafidz & Hafidzah group and the Al Maghfirah Taklim Council, Al Ikhas Mosque, Pinrang Rutan, using the Da'wah Bil-Hikmah method, namely conveying da'wah in a wise and wise manner and Mauizatil Khazanah (Good Advice) is giving good advice so that people will love goodness and stay away from evil.